Cost-effectiveness of Same-day Discharge Surgery for Primary Total Hip Arthroplasty: A Pragmatic Randomized Controlled Study - Shi, Yangyang; Zhu, Peipei; Jia, Jie; Shao, Zengwu; Yang, Shuhua; Chen, Wei; Zhang, Ke; Tong, Wei; Tian, Hongtao (Frontiers in Public Health, 2022)
Background：Total hip arthroplasty (THA) causes a great medical burden globally, and the same-day discharge (SDD) method has previously been considered to be cost saving. However, a standard cost-effectiveness analysis (CEA) in a randomized controlled trial (RCT) is needed to evaluated the benefits of SDD when performing THA from the perspective of both economic and clinical outcomes. Methods： 84 participants undergoing primary THA were randomized to either the SDD group or the inpatient group. Outcomes were assessed by an independent orthopedist who was not in the surgical team, using the Oxford Hip Score (OHS), EuroQol 5D (EQ-5D), SF-36 scores and the quality-adjusted life years (QALYs). All the cost information was also collected. Results： The mean stay of patients in the SDD group was 21.70 ± 3.45 hours, while the inpatient group was 78.15 ± 26.36 hours. This trial did not detect any significant differences in OHS and QALYs. The total cost in the SDD group was significantly lower than that in the inpatient group (¥69771.27 ± 6608.00 vs. ¥80666.17 ± 8421.96, p < 0.001). From the perspective of total cost, when measuring OHS, the incremental effect was -0.12 and the incremental cost was -¥10894.90. The mean incremental cost-effectiveness ratio (ICER) was 90790.83. When measuring QALYs, the incremental effect was 0.02, and the ICER was negative. Sensitivity analysis produced similar results. Conclusions： SDD has an acceptable likelihood of being more cost-effective than the traditional inpatient option. After conducting cost–utility analysis, SDD resulted in better QALYs, while significantly reducing the total cost.